Огляд сучасних технологій ефективної розробки програмного забезпечення - Самойленко, О.А. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2010)
The paper considers technologies of designing and developing software that can be used to create a combined system for information support of managerial decisions. The main architectural parts of the system are considered. The main capabilities and features of the contemporary technologies using that provide effectiveness and quality of the whole system developing as well as every part separately are presented.